SHIELD DRIVE Science Center: Efforts in diversification and inclusion in heliophysics - Buxner, Sanlyn; Gross, Nicholas; Opher, Merav; Wong, Joyce; Richardson, John (Frontiers in Astronomy and Space Sciences, 2023)
We present the broader impacts effort of the NASA SHIELD DRIVE Science Center, summarizing both phase I and now phase II efforts. The purpose of the broadening impact efforts are to address the overall lack of diversity in the space physics workforce through intentional programming intended to increase inclusiveness and explicit support for emerging and early career researchers. Specific efforts include an online repository of testimonials of diverse early career researchers, SHIELD webinars highlighting the human side of eminent scientists, support for REU students at different institutions, and a yearly heliophysics summer school. We also discuss efforts to support heliophysics scientists through community building events and ongoing training. The SHIELD Drive Science Center’s overall broadening impact goal is to train and mentor the next generation of team-based heliophysicists while accelerating knowledge integration, transfer, and communication across traditional boundaries.